SUPERVISION OF WIRETAPPING AUTHORITY BY THE CORRUPTION ERADICATION COMMISSION (KPK) FROM A HUMAN RIGHTS PERSPECTIVE - Gunawan Widjaja; Adrian Bima Putra (ADISAM PUBLISHER, 2025)
This study aims to analyse the monitoring mechanism of the Corruption Eradication Commission's (KPK) wiretapping authority from a human rights perspective. The research method used is normative juridical with a literature study approach, which examines various laws and regulations, court decisions, and relevant legal literature. The results showed that the tapping supervision mechanism by the KPK Supervisory Board still has various weaknesses, such as potential conflicts of interest, risk of information leakage, and unclear standard procedures. In addition, administrative supervision has not been able to fully guarantee the protection of privacy and human rights. Therefore, it is necessary to optimise a more proportional supervision model, through regulatory reform, strengthening independent external supervision, and utilising technology to increase transparency and accountability. This effort is expected to create a balance between the effectiveness of corruption eradication and the protection of human rights in Indonesia